Laser therapy in the treatment of peripheral neuropathy induced using paclitaxel in breast cancer: An integrative review - Silva , Suzana Grings de Oliveira da; Garcia , Yanka Eslabão; Bueno , Kimberly; Rabin, Eliane Goldberg; Trevisan , Bibiana Fernandes; Reyes , Vanessa Belo; Oliveira , Mariana Cardoso de; Matos , Maryana Schwartzhaupt de; Pereira , Carla Patrícia Michelotti (Seven Editora, 2023)
Objective: To synthesize knowledge about the use of photobiomodulation for the treatment of peripheral neuropathies induced by paclitaxel, seeking evidence for the care of patients undergoing treatment for breast cancer. Method: this is an integrative review between the years 2018 and 2023, using the Embase, Latin American and Caribbean Health Sciences Literature (LILACS), and PubMed databases. Results: 28 articles that met the inclusion criteria were reviewed, of which, based on the most prevalent outcomes, three topics were evidenced that discuss chemotherapy-induced peripheral neuropathy; treatments used; and photobiomodulation and peripheral neuropathy. Conclusions: paclitaxel proved to be the main causative agent of neurotoxicity, requiring urgent coping strategies. The benefits evidenced by photobiomodulation therapy in peripheral neuropathies are directly proportional to the damage that paclitaxel causes to the peripheral nerve, providing recovery from deterioration. DOI:https://doi.org/10.56238/sevened2023.004-025